2021
DOI: 10.1021/acsenergylett.1c00743
|View full text |Cite
|
Sign up to set email alerts
|

ENPOLITE: Comparing Lithium-Ion Cells across Energy, Power, Lifetime, and Temperature

Abstract: Lithium-Ion battery lifetimes from cyclic and calendar aging tests of more than 1000 cells were compared employing novel plots termed ENPOLITE (energy-power-lifetime-temperature). Battery cell data from in-house measurements and published data were combined into a uniform database; the total dataset size exceeds 1000 GB. At a glance, ENPOLITE plots inform about the nominal capacity, cell format, cell chemistry, average aging test duration, measurement temperature, specific power employed for testing, energy de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…In order to encourage comparison with other ageing studies in the field, this data is further presented in an ENPOLITE-style plot (Fig. 6b) as described in [26], which additionally demonstrates increasing power capability and cyclability over subsequent cell generations. Interestingly, a decrease in both the used specific power and used specific energy parameters is observed between cell types A and B.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…In order to encourage comparison with other ageing studies in the field, this data is further presented in an ENPOLITE-style plot (Fig. 6b) as described in [26], which additionally demonstrates increasing power capability and cyclability over subsequent cell generations. Interestingly, a decrease in both the used specific power and used specific energy parameters is observed between cell types A and B.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…6. Evolution of (a) volumetric energy density and nominal specific energy and (b) ENPOLITE-style plot evaluating used specific power, used specific energy, and lifetime as described in [26]. Study of cell type D (2018) and beyond is ongoing and their cyclability is not yet reported.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Out of the three commonly used cell formats, literature is generally considering decreasing energy densities from cylindrical to pouch to prismatic cells. [23,[37][38][39] Furthermore, widely scattered values and ranges for volumetric energy densities are being cited. [23,38,40] In the VDMA Battery Production Report for 2020, prismatic cells are listed at 550 Wh L À1 , pouch at 600 Wh L À1 , and cylindrical at 850 Wh L À1 .…”
Section: Prismatic Cells Pouch Cellsmentioning
confidence: 99%
“…[23,[37][38][39] Furthermore, widely scattered values and ranges for volumetric energy densities are being cited. [23,38,40] In the VDMA Battery Production Report for 2020, prismatic cells are listed at 550 Wh L À1 , pouch at 600 Wh L À1 , and cylindrical at 850 Wh L À1 . For 2025 prismatic cells with 700 Wh L À1 , pouch cells with 800 Wh L À1 , and cylindrical cells with more than 950 Wh L À1 are expected.…”
Section: Prismatic Cells Pouch Cellsmentioning
confidence: 99%
“…We note that the energy density calculation here is based on the theoretical values of cathode and anode only. For the energy density estimation of a Li-ion full battery, many other parameters, including areal loading density, weight of current collectors and electrolytes, initial capacity balance between the anode and cathode, and initial Coulombic efficiency, should be considered. , Although there is hardly any report on the energy density of a full battery utilizing oxide or sulfide anodes, we argue that these full batteries could obtain energy density lower than that of the full batteries with graphite anodes, as the initial Coulombic efficiency and cycle stability are both remarkably lower than that of graphite. Furthermore, most of the recently published data on batteries, whose energy density exceeds 300 Wh kg –1 , used Li metal or Si-based anodes .…”
mentioning
confidence: 92%